Sustaining the Township Economy: An Investigation into the Factors Influencing the Shopping Experience of Spaza Shop Customers in South Africa - van Eyk, Marle; Amoah, Felix; Yase, Thembelihle (Journal of Economics and Behavioral Studies, 2022)
The township economy supports many South Africans by creating employment and reducing the socio-economic challenges facing the country. To ensure sustainable growth of the sector, research is required on key businesses within the informal economy. This study empirically investigated the factors influencing the shopping experience of spaza shop customers in South Africa. Spaza shops, an under-researched South African context, continue to expand in various townships and serves as retail outlet where consumers purchase their daily products and services. The study embraced a quantitative research design. A self-administered questionnaire was employed to collect the data for the study. The target respondents include customers who were older than 18 years and had previously purchased from spaza shops. Respondents were selected using convenience sampling. The questionnaires were distributed to six townships in South Africa. 185 usable questionnaires were included in the data analysis. The empirical results provided evidence that supports the existence of statistically significant positive correlations between five independent experience factors, namely: esthetic, distinctiveness, cognitive, affective and social; with customer experience (dependent variable). Additionally, three of the five experience factors (social, affective and cognitive) are significant predictors of customer experience in the context of this study. Based on the identified factors, several recommendations are made for improving customer experience in a spaza shop context. Recommendations made are expected to enhance the competitiveness of spaza shops thereby enabling them to increase their contribution to employment creation and national Gross Domestic Product.